(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The article investigates the basics of formation of the notion "creativin", studies the essence of the notion of creative activity of music teacher as an important pedagogical component; considers new scientific approaches to the research of teacher’s professional development and growth of its creative activity level.